Comparing the Outcomes of Anti-VEGF Treatment for Choroidal Neovascular Membrane (Community Based Medical Journal, 2024)
This quasi-experimental study was conducted in the Department of Ophthalmology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, and Bangladesh Eye Hospital, Dhaka, Bangladesh, from March 2020 to August 2021, to compare the efficacy of Bevacizumab and Ranibizumab on patients with choroidal neovascular membrane (CNVM) due to age-related macular degeneration (AMD). A total of 34 eyes of 34 participants with CNVM in AMD divided into Group A, received monthly intravitreal ranibizumab (0.5 mg in 0.05 ml) and Group B, bevacizumab (1.25 mg in 0.05 ml) for 3 consecutive months. Before treatment, mean BCVA was found 37.9412±16.68259 in group A and 35.2941±12.68249 in group B. After treatment, the mean best-corrected visual acuity (BCVA) was found 53.5294±14.97547 in group A and 48.8235±13.75334 in group B. The differences were not statistically significant (p>0.05) between two groups. The improvement in BCVA was highly significant (p0.05) between two groups. However, the improvement by decreasing macular thickness was highly significant (p